PENERAPAN GOOD GOVERNMENT DAN ELECTORAL GOVERNANCE STUDI DEMOKRASI INDONESIA PADA PENYELENGGARAAN PILKADA TAHUN 2024 - Hidayat, Novendra; Febriansyah, Ricky (Jurnal Inovasi Daerah, 2024)
2024 is the year of Indonesian democracy, by holding general elections and regional elections simultaneously. The progress of democracy is marked by the link between good government and electoral governance, particulary regarding the issue of information disclosure in implementing electronic-based government systems in general and regional elections. This article aims to describe the implementation of good governance and electoral governance in the development of democracy in Indonesia in 2024. By using inductive grounded theory research methods from research on democratic phenomena, compiling evidence through theory and field phenomena as well as strategies needed to resolve election disputes. Achieving this also requires the principles of governance in realizing a democratic government. In its development is the implementation of election digitalization through processes, open election data and results so that public trust arises. The General Elections Commission (KPU) should strive to support information transparency through developing information systems in elections. Even though in reality there are obstacles and pressure from various scientific experts regarding information disclosure KPU is committed to developing information transparency so that the public does not get misunderstandings in the application of the information system owned by KPU. The public is waiting for efforts to improve information disclosure in the 2024 election to become a record of the regional elections and subsequent elections. The conclusion of this research is that KPU provides autthority to local KPU in giving understanding to operate information system more comprehensively, and provides supporting infrastructure so that information system may run maximally.